A Silent Dissection Complicating Myocardial Infarction: A Case Report - Adithya Shelley; Akshat Sharma; Jostol Pinto (Journal of Clinical and Diagnostic Research)
A Left Ventricular (LV) pseudoaneurysm develops when free myocardial wall rupture is contained by an adherent layer of overlying pericardium and scar tissue. It is a rare mechanical complication seen in 0.2% of patients post Myocardial Infarction (MI). Furthermore, it remains a challenge to diagnose and differentiate it from a true aneurysm due to overlapping clinical presentations and echocardiographic findings. A 40-year-old male patient presented with ST Elevation Myocardial Infarction (STEMI) and received guideline directed management. However, he was later found to have a pansystolic murmur at the apex and an early diastolic murmur over the left lower sternal border (to and fro murmur) on auscultation. An echocardiogram had subsequently revealed a dissecting pseudoaneurysm of the left ventricle and Contrast-enhanced Computed Tomography (CECT) confirmed the presence of an anterior dissecting pseudoaneurysm. This is an atypical presentation of a niche post MI complication due to its asymptomatic presentation, atypical location and unique anatomy despite prompt revascularisation. Furthermore, the authors emphasise the importance of cardiac auscultation on a day-to-day basis and high index of suspicion to ensure early diagnosis and management of such a silent, calamitous complication.